2019
DOI: 10.3390/molecules24071422
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lactococcus lactis Gh1 with Gum Arabic and Synsepalum dulcificum via Spray Drying for Potential Inclusion in Functional Yogurt

Abstract: There has been an explosion of probiotic incorporated based product. However, many reports indicated that most of the probiotics have failed to survive in high quantity, which has limited their effectiveness in most functional foods. Thus, to overcome this problem, microencapsulation is considered to be a promising process. In this study, Lactococcus lactis Gh1 was encapsulated via spray-drying with gum Arabic together with Synsepalum dulcificum or commonly known as miracle fruit. It was observed that after sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 65 publications
1
36
2
1
Order By: Relevance
“…The different methods for the microencapsulation of probiotic microorganisms involved several physical and chemical principles. Successful methods used in the microencapsulation of probiotics include: spray drying [21,22]; spray chilling (also called spray cooling or congealing) [23,24]; spray freeze drying [25,26]; lyophilisation [27,28]; electrospraying [29,30]; layer-by-layer [31,32]; fluidised bed drying [33,34]; extrusion [35,36] and its improved version: the vibrating nozzle technology [37,38]. Emulsification [39,40] and coacervation [41,42] are other important and often used physicochemical techniques.…”
Section: Methods For Microencapsulation Of Probioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The different methods for the microencapsulation of probiotic microorganisms involved several physical and chemical principles. Successful methods used in the microencapsulation of probiotics include: spray drying [21,22]; spray chilling (also called spray cooling or congealing) [23,24]; spray freeze drying [25,26]; lyophilisation [27,28]; electrospraying [29,30]; layer-by-layer [31,32]; fluidised bed drying [33,34]; extrusion [35,36] and its improved version: the vibrating nozzle technology [37,38]. Emulsification [39,40] and coacervation [41,42] are other important and often used physicochemical techniques.…”
Section: Methods For Microencapsulation Of Probioticsmentioning
confidence: 99%
“…On the other hand, the protein moiety of GA provides the surface activity, foaming abilities, and emulsifying characteristics of this polysaccharide [178,195]. In this regard, combinations of gelatine-GA [67], whey protein isolate (WPI)-GA [58], and the individual mixture of seed, leaf, or pulp extracts of the miracle fruit (Synsepalum dulcificum) with GA [21], were used as coating materials for the microencapsulation of probiotics and these coatings successfully improved the survival of probiotic cells during processing, simulated gastrointestinal in vitro conditions, and upon storage, when compared to free cells.…”
Section: Anionic Polysaccharidesmentioning
confidence: 99%
“…Spray-drying is the most cost-effective microencapsulation method for probiotic bacteria, and it is suitable for large-scale and industrial applications (Fazilah et al, 2019;Macías-Cortés et al, 2019). Likewise, spray-drying is a suitable method to preserve the viability of microorganisms (Mirković et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotic foods most commonly contain the Gram-positive lactic acid bacteria Lactobacillus and Bifidobacterium [8]. Other bacteria such as Lactococcus, Bacillus, Pediococcus, and Streptococcus are also used in probiotic research today [9,10]. Main yeasts, such as Saccharomyces, have also been studied (table 1), along with other genera such as Kluyveromyces, Pichia, and Candida [11].…”
Section: Biomarkers Of Probioticsmentioning
confidence: 99%
“…On the other end of the spectrum, others have also observed that many probiotic foods failed to survive in high quantity, limiting their effectiveness as functional foods. Thus, Fazilah et al [10] set out to increase survival rate by encapsulating Lactococcus lactis cells with gum arabic and Synsepalum dulcificum, which led to a higher viability than non-encapsulated cells. Much research has been conducted on how dairy products affect the human microbiome, and more is required to establish a consensus.…”
Section: Probiotic Bacteria In Food Dairy Productsmentioning
confidence: 99%